أسواق الأندلس دراسة في نشأتها، عوامل تطورها وأثرها في المجتمع 138 – 422 هج / 756 – 1031م - أبو القاسم, جميلة محمد صالح (Al-Qurtas, 2026)
أسواق الأندلس دراسة في نشأتها، عوامل تطورها وأثرها في المجتمع 138 – 422 هج / 756 – 1031م